2006
DOI: 10.28945/247
|View full text |Cite
|
Sign up to set email alerts
|

On the Development of a Programming Teaching Tool: The Effect of Teaching by Templates on the Learning Process

Abstract: On the Development of a Programming Teaching Tool 272-providing a web-based self learning tool that will reduce the need for teaching and learning assistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 25 publications
0
23
0
1
Order By: Relevance
“…However in the last years new studies have been performed on the educational impact of programming using new visual programming languages based on blocks (Weintrop & Wilensky, 2015), the most notable example being Scratch (Maloney, Resnick, Rusk, Silverman, & Eastmond, 2010), which try to address one of the major issues related to teaching introductory programming courses: the amount of time spent on the language's syntax (Al-Imamy, Alizadeh, & Nour, 2006). In the development of Scratch, creators were inspired and informed by the success and posterior decline in the use of Logo and other previous programming languages, aiming to make Scratch more meaningful for learners, more tinkerable, and more social (Resnick et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However in the last years new studies have been performed on the educational impact of programming using new visual programming languages based on blocks (Weintrop & Wilensky, 2015), the most notable example being Scratch (Maloney, Resnick, Rusk, Silverman, & Eastmond, 2010), which try to address one of the major issues related to teaching introductory programming courses: the amount of time spent on the language's syntax (Al-Imamy, Alizadeh, & Nour, 2006). In the development of Scratch, creators were inspired and informed by the success and posterior decline in the use of Logo and other previous programming languages, aiming to make Scratch more meaningful for learners, more tinkerable, and more social (Resnick et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Programming requires the understanding of a variety of different educational areas; for example, the novice programmer must digest logic and mathematical concepts, syntax, the language interface, algorithms, flowcharts, and pseudocode associated with programming theory, overwhelming even the optimal e-learner; thus, they experience increased levels of stress and frustration (Kelleher & Pausch, 2005). Similarly, (Al-Imamy, 2006) showed that the primary obstacle in teaching introductory programming is the critical task of teaching syntax, which reduces the time allocated for teaching learners how to design programs through algorithms, flowcharts, and pseudocode that enhance the ability of the learners to creatively find solutions to the programming problems they face. The authors stipulated that diverse learner experiences, both life and scholastic, coupled with the restrictions presented by the online environment reduce the course to syntactic rules, disregarding problem-solving concepts critical to programming (Al-Imamy, 2006).…”
Section: Teaching Programming In the Online Environmentmentioning
confidence: 99%
“…Literature cites two fundamental issues related to teaching programming: the selection of a programming language and the most effective approach for teaching computer programming (Al-lmamy, Alizadeh & Nour, 2006;Ottaway, & Chang, 2006;Parker, Chao). We focus on the teaching approach, which continues to be problematic as educators experiment with various paradigms in an attempt to enhance engagement of students.…”
Section: Introductionmentioning
confidence: 99%